2017
DOI: 10.1371/journal.pcbi.1005625
|View full text |Cite
|
Sign up to set email alerts
|

Identifying direct contacts between protein complex subunits from their conditional dependence in proteomics datasets

Abstract: Determining the three dimensional arrangement of proteins in a complex is highly beneficial for uncovering mechanistic function and interpreting genetic variation in coding genes comprising protein complexes. There are several methods for determining co-complex interactions between proteins, among them co-fractionation / mass spectrometry (CF-MS), but it remains difficult to identify directly contacting subunits within a multi-protein complex. Correlation analysis of CF-MS profiles shows promise in detecting p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
2

Relationship

5
4

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 56 publications
1
25
0
Order By: Relevance
“…In summary, we believe that, as quantitative microbiome profiling will become increasingly available, the semi-parametric rank-based estimators for correlation and partial correlation estimation discussed here provide an important tool for reliable statistical analysis of quantitative microbiome data. While we have focused here on targeted amplicon-based sequencing datasets, our methodology is broadly applicable to other biological high-throughput data with large excess of zero counts, including quantitative metagenomics (Satinsky et al, 2013), single-cell RNA-Seq data (see Risso et al (2018) for a recent statistical analysis framework), and mass spectrometry proteomics data (Drew et al, 2017). Moreover, the concept of latent correlation employed in SPRING can naturally generalize to joint analysis of multiomics dataset when, on the same sample, several zero-inflated data types are measured in tandem.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, we believe that, as quantitative microbiome profiling will become increasingly available, the semi-parametric rank-based estimators for correlation and partial correlation estimation discussed here provide an important tool for reliable statistical analysis of quantitative microbiome data. While we have focused here on targeted amplicon-based sequencing datasets, our methodology is broadly applicable to other biological high-throughput data with large excess of zero counts, including quantitative metagenomics (Satinsky et al, 2013), single-cell RNA-Seq data (see Risso et al (2018) for a recent statistical analysis framework), and mass spectrometry proteomics data (Drew et al, 2017). Moreover, the concept of latent correlation employed in SPRING can naturally generalize to joint analysis of multiomics dataset when, on the same sample, several zero-inflated data types are measured in tandem.…”
Section: Discussionmentioning
confidence: 99%
“…A characteristic of PPIs measured by co-fractionation is that it is not known which interactions are direct and which are transitive ( i.e ., as between subunits of the same complex that do not directly contact one another) (Drew et al, 2017a(Drew et al, , 2017b . Though reporting the hierarchical tree of interactions, rather than flat clusters, can help disentangle this issue, XL-MS can provide empirical evidence of direct interactions, and our interaction map determined from XL-MS, though much smaller, still significantly overlaps the co-fractionation map ( Supplemental Figure 1 ).…”
Section: Cross-linking Provides Structural Support For Co-fractionatimentioning
confidence: 99%
“…In an effort to understand why proteins form these machines, proteome-wide studies have been conducted to determine the composition of protein complexes (Drew et al, 2017a; Gavin et al, 2002; Havugimana et al, 2012; Hein et al, 2015; Ho et al, 2002; Huttlin et al, 2015, 2017; Kastritis et al, 2017; Kristensen et al, 2012; Krogan et al, 2006; Wan et al, 2015). Similar studies have identified direct contacts between protein complex subunits computationally (Drew et al, 2017b) or by cross-linking mass spectrometry (Leitner et al, 2016; Liu and Heck, 2015; Rappsilber et al, 2000), and while these studies provide insightful predictions on protein-protein interactions, they lack directly observable structural information that can inform us on function and subunit stoichiometry.…”
Section: Introductionmentioning
confidence: 99%